2021
DOI: 10.1007/978-981-15-7850-2_15
|View full text |Cite
|
Sign up to set email alerts
|

Beijing Union Medical College Hospital and China’s Modern Medical Development

Abstract: We study the nonlinear localized modes in two-component Bose-Einstein condensates with parity-time-symmetric Scarf-II potential, which can be described by the coupled Gross-Pitaevskii equations. Firstly, we investigate the linear stability of the nonlinear modes in the focusing and defocusing cases, and get the stable and unstable domains of nonlinear localized modes. Then we validate the results by evolving them with 5% perturbations as an initial condition. Finally, we get stable solitons by considering exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 190 publications
1
23
0
Order By: Relevance
“…Main efficacy indicators: total efficiency: refer to the Guidelines for Clinical Research of New Chinese Medicine Drugs , [20] total effective rate = (effective number + effective number)/total number of patients ×100%. significant effect: clinical symptom score decreased ≥60%, Ccr increased ≥20% or Scr decreased ≥20%; effective: 30%≤ clinical symptom score decreased <60%, 10%≤ Ccr increased <20% or 10%≤ Scr decreased <20%; stable: clinical symptom score decreased by <30%, Ccr increased by <10% or Scr decreased by <10%; invalid: the clinical symptoms were not improved or aggravated, the clearance rate of Ccr decreased, and the Scr increased.…”
Section: Methodsmentioning
confidence: 99%
“…Main efficacy indicators: total efficiency: refer to the Guidelines for Clinical Research of New Chinese Medicine Drugs , [20] total effective rate = (effective number + effective number)/total number of patients ×100%. significant effect: clinical symptom score decreased ≥60%, Ccr increased ≥20% or Scr decreased ≥20%; effective: 30%≤ clinical symptom score decreased <60%, 10%≤ Ccr increased <20% or 10%≤ Scr decreased <20%; stable: clinical symptom score decreased by <30%, Ccr increased by <10% or Scr decreased by <10%; invalid: the clinical symptoms were not improved or aggravated, the clearance rate of Ccr decreased, and the Scr increased.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of high supersaturation, the F-faces grow through the 2D nucleation, and the growth rate can be approximated as 31 (2) where F is defined as (3) in which c n is the factor defined as c n � P/A 1/2 , where P is the perimeter of a nucleus and A is the area; and ϕ e is the effective edge energy. The absolute face growth rate can be calculated by the Lovette-Doherty equation 31 (4) where σ* is an arbitrary low supersaturation at which all faces are grown in the spiral growth pattern and σ 2D,hkl is the onset supersaturation for the 2D nucleation.…”
Section: Ae Modelmentioning
confidence: 99%
“…It is not only intrinsically determined by molecular structure and molecular stacking structures but also significantly governed by crystallization conditions, such as temperature, solvent, agitation, seed, container size and shape, etc. 2 The crystal morphology of an energetic compound governs many fundamental properties and use behaviors, including energy, sensitivity, stability, processing performance, and so forth, as demonstrated in Figure 1. For example, when the morphology of an energetic crystal changes from spherical to ellipsoidal, prism-like, tetrahedral, and needle-like, its mechanical sensitivity increases, as chemical decomposition and hot spot formation proceed more and more readily on edges and corners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it has been reported that enflurane could drive EEG epilepsy-like movement. Moreover, fluothane and enflurane could significantly impair the automatic regulatory mechanism (Huang GY, et al, 2000). It has been found that fluothane, sevoflurane, desflurane, isoflurane all could reduce the volume of cerebral infarction in focal cerebral ischemia, and this protective effect occurs on 1 to 7 days (d) following ischemia (Xiong L, et al, 2003).…”
Section: Neuroprotective Role Of Inhaled Anestheticsmentioning
confidence: 99%